Symposium 4: Examining Conceptions of E-Learning in an Intercultural, Sino-UK, Context - McConnell, David; Banks, Sheena; Bowskill, Nicholas (Proceedings of the International Conference on Networked Learning, 2008)
The focus of this paper is on conceptions of learning and teaching in the context of a cross-national, Sino-UK project funded by Hefce that is examining the design and impact of e-learning, and e-learning delivery, in China and the UK. The central aim of this project is to consider teacher beliefs and conceptions in both countries, and how they impact on e-learning pedagogic practice. The paper discusses the findings from two large-scale interview studies of teachers’ conceptions of e-learning. One study was conducted in China and involved interviewing 20 higher education teachers and other personnel about their conceptions of e-learning and teaching. The other study was carried out in the UK, and involved interviewing 15 higher education teachers about their conceptions of e-learning. Our research into Chinese higher education teacher’s conceptions of e-learning resulted in a set of preliminary conceptual categories in which those interviewed expressed their conceptions of e-learning. The categories were: ’centrality of the lecture’, ’online cooperative learning’, ’network learning’, ’student learning’, and ’infrastructure and access’. Our research into UK higher education teachers’ conceptions of e-learning produced a set of categories in some ways qualitatively different to those resulting from the interviews in China. These were: "community", "rhythms and design" and "leadership and strategy". The paper considers the preliminary results from a comparison of the conceptions of e-learning of higher education teachers in China and the UK.